Basic study on traffic safety in Metro Manila traffic accidents in Quezon City - Regidor, Jose Regin F. (Philippine Engineering Journal)
This report presents and discusses concepts, prevailing conditions and issues in the Philippines, and examines a 2-year accident data set for Quezon City, the largest among the cities and municipalities composing Metro Manila. Based on this information, the paper proposes several countermeasures for improvement of the traffic safety situation.